Medieval Futurity : Essays for the Future of a Queer Medieval Studies - Will, Rogers; Will, Rogers; Roman, Christopher Michael; Roman, Christopher Michael; Rogers, Will; Rogers, Will; Michelle M., Sauer; Michelle M., Sauer; Michael, Johnson; Michael, Johnson; Micah, Goodrich; Micah, Goodrich; et al. (Book collections on Project MUSE., 2020)
This collection of essays asks contributors to take the capaciousness of the word "queer" to heart in order to think about what medieval queers would have looked like and how they may have existed on the margins and borders of dominant, normative sexuality and desire. The contributors work with recent trends in queer medieval studies, blending together modern concepts of sexuality and desire with the queer configurations of eroticism, desire, and materiality as they might have existed for medieval audiences.